Dorsal Fracture-Dislocations of the Proximal Interphalangeal Joint: Evaluation of Closed Reduction and Percutaneous Kirschner wire Pinning. (March 2015) - Haseth, Kristin B. de; Neuhaus, Valentin; Mudgal, Chaitanya S.
Background: The purpose of this study is to evaluate the outcome of closed reduction and percutaneous Kirschner wire pinning in acute dorsal fracture-dislocations of the proximal interphalangeal (PIP) joint. Methods: Eight men and one woman were treated with closed reduction and percutaneous Kirschner wire pinning by one orthopaedic surgeon. The ring finger was injured in six patients, the small finger in two patients and the middle finger in one patient. The mean joint surface involvement was 36 % (range, 26–49 %). The Kirschner wires were removed after an average of 28 days (range, 24–37 days). Results: All patients demonstrated a painless, but fusiform, swollen PIP joint after a mean follow-up of 6.5 months. The average flexion of the PIP joint was 106° (range, 80–110), and the average extension of the PIP joint was 4° short of full extension (range, 10 hyperextension–15 flexion contracture). All patients had a concentrically reduced PIP joint with a healed fracture on radiographs. Two patients had radiographic evidence of degenerative changes, but were asymptomatic. One patient developed a superficial pin track infection, which quickly resolved with a short course of antibiotics, and avascular necrosis affecting one of the condyles of the proximal phalanx. Conclusions: In agreement with previous studies, closed reduction and percutaneous Kirschner wire pinning in dorsal fracture-dislocations of the PIP joint is a minimally invasive and simple technique which appears to give satisfactory outcomes in the short to intermediate term.